Evaluation Of Midwifery Care In Trimester III Pregnant Women With Waist Pain - Liontin Valentina Febriani; Septi Maisyaroh Ulina Panggabean; Netty Herawaty Purba (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Pregnancy, Low back pain is discomfort that occurs below the ribs and above the inferior gluteal area. One of the causes of low back pain is due to hormonal changes that cause changes in the supporting and connecting soft tissues resulting in decreased muscle elasticity and flexibility and also occurs due to increasing gestational age. Increasing low back pain is seen as the pregnancy progresses. According to research, the higher the number of pregnancies, the risk of back pain will increase. The negative impact of low back pain is that it can cause a decrease in the quality of life of pregnant women due to disruption of daily physical activities. Objectives: The purpose of the study was to evaluate the results of midwifery care provided to third-trimester pregnant women with low back pain. Methods: The method used by the researcher is descriptive through a midwifery management approach and is documented with SOAP. Results: The results of this study showed that pregnant women with low back pain after being given massage therapy felt that the pain had decreased. Conclusion: The conclusion of this study shows that massage therapy affects reducing pain in the lower back that pregnant women feel in the third trimester.